Correction: Bhutani et al. Doxorubicin-Induced Cardiotoxicity: A Comprehensive Update. J. Cardiovasc. Dev. Dis. 2025, 12, 207 - Vasvi Bhutani; Fahimeh Varzideh; Scott Wilson; Urna Kansakar; Stanislovas S. Jankauskas; Gaetano Santulli (Journal of Cardiovascular Development and Disease, 2025)
In the original publication [...]